A detailed review on current status of energy efficiency improvement in the Swiss industry sector. (February 2020) - Zuberi, M. Jibran S.; Santoro, Marina; Eberle, Armin; Bhadbhade, Navdeep; Sulzer, Sabine; Wellig, Beat; Patel, Martin K.
Abstract: While quantitative methods for tracking the evolution of energy efficiency (EE) in industry do exist, these cannot always be directly applied, mainly due to lack of data on physical activity levels, as encountered in Switzerland. Therefore, a bottom-up method is developed and tested for estimating the sectoral physical activity levels in Switzerland. On this basis, sector-specific EE indices are determined. The results show that during the period 2009–2016, EE improved most in the paper sector (3.3% p.a.), followed by minerals (2.3% p.a.) and food (1.6% p.a.) sectors while the levels have remained approximately unchanged in chemical and metal sectors. Furthermore, the annual change in final energy demand was decomposed into changes of physical production, price levels and EE. The analysis concluded that only the food sector performed well according to all performance indicators. The detailed analysis of the Swiss target agreements' data has revealed major final energy savings in chemical and food sectors during the period 2000–2016. Among the different categories of EE measures, process related measures have proven to yield the highest energy savings across all sectors. The results indicate the successful implementation of EE measures in Swiss industry, favored by the relatively strict Swiss regulatory framework and its target agreement mechanism. Highlights: A bottom-up method is developed for estimating the Swiss physical activity levels. Sector-specific energy efficiency indices are determined and analyzed. A detailed analysis of the data on Swiss target agreements is done.